Profile of COVID-19 patients in COVID dedicated tertiary care centre in Himachal Pradesh: a prospective observational cross sectional study - Lal, Roshan; Bhawani, Rajesh K.; Dheer, Santosh K.; Kumar, Nitesh; Kumar, Soni (International Journal of Research in Medical Sciences, 2021)
Background: COVID-19 pandemic originated in China in December 2019 and fumed in whole world over few months. Millions of deaths have occurred worldwide till now because of this pandemic. Causative agent was identified as severe acute respiratory syndrome corona virus 2 (SARS-CoV-2) causing viral pneumonia and serious manifestations were seen in association with increased age and comorbidies. Methods: This study was planned in very initial stage of pandemic in our country to study the profile of COVID-19 patients. This study was conducted over a period of six months from April 2020 to September 2020 at SLBSGMCH, Mandi at Nerchowk. Results: 202 patients were enrolled for this study with mean age of presentation 48 years, 61 were females, 147 (72%) were senior citizens, most patients were from district Mandi and most common symptoms were fever (58%), cough (46%), shortness of breath (35%) and associated commonest comorbidities were hypertension (HTN) (29%) and diabetes (23%). Median neutrophil to lymphocyte ratio (NLR) was higher (5.47) in moderate to severe disease and associated with poor outcome. All the 11 patients who were put on support of ventilator, succumbed to death. Conclusions: Most common symptoms were fever, cough, shortness of breath and most common comorbidty was HTN. Comorbidity, increased age and higher NLR were risk factors for severity and poor outcome. More research is needed to save mankind from this pandemic as still no specific therapy is available against this virus.